Psychological Well-Being Women Workers Multiple Role in Bandung: Analysis of Stress And Aggression of Children - Zakariyya, Farhan; Wyandini, Diah Zaleha; Wulandari, Anastasia (Faculty of Psychology, Universitas Gadjah Mada, 2024)
This study aims to obtain empirical data on the psychological well-being of female employees in Bandung related to work stress and aggression towards children. The method used in this study is a survey method with data collection techniques using purposive sampling. Research respondents are female employees who have dual roles as housewives and as employees in Greater Bandung. The research instruments used were Psychological well-being, Perceived Stress Questionnaire, and Aggression Scale towards children. The data analysis technique of this research is multiple regression analysis. The regression test results stress and aggression in children have a significant positive impact in predicting psychological well-being (F=25.392, P=<0.001).The psychological well-being of female employees in Greater Bandung can be influenced by stress and aggression towards children. This research can be the basis of policy making for working women who have dual roles in controlling stress and the ability to manage aggression to improve psychological well being.